Characterization of C-X-C chemokine receptor type 5 in the cornea and role in the inflammatory response after corneal injury. (January 2023) - Balne, Praveen K.; Gupta, Suneel; Landon, Keele M.; Sinha, Nishant R.; Hofmann, Alexandria C.; Hauser, Nicholas; Sinha, Prashant R.; Huang, Hu; Kempuraj, Duraisamy; Mohan, Rajiv R.
Abstract: C-X-C chemokine receptor type 5 (CXCR5) regulates inflammatory responses in ocular and non-ocular tissues. However, its expression and role in the cornea are still unknown. Here, we report the expression of CXCR5 in human cornea in vitro and mouse corneas in vivo, and its functional role in corneal inflammation using C57BL/6J wild-type ( CXCR5 +/+ ) and CXCR5 -deficient ( CXCR5 −/− ) mice, topical alkali injury, clinical eye imaging, histology, immunofluorescence, PCR, qRT-PCR, and western blotting. Human corneal epithelial cells, stromal fibroblasts, and endothelial cells demonstrated CXCR5 mRNA and protein expression in PCR, and Western blot analyses, respectively. To study the functional role of CXCR5 in vivo, mice were divided into four groups: Group-1 ( CXCR5 +/+ alkali injured cornea; n = 30), Group-2 ( CXCR5 −/− alkali injured cornea; n = 30), Group-3 ( CXCR5 +/+ naïve cornea; n = 30), and Group-4 ( CXCR5 −/− naïve cornea; n = 30). Only one eye was wounded with alkali. Clinical corneal evaluation and imaging were performed before and after injury. Mice were euthanized 4 h, 3 days, or 7 days after injury, eyes were excised and used for histology, immunofluorescence, and qRT-PCR. In clinical eye examinations, CXCR5 −/− mouse corneas showed ocular health akin to the naïve corneas. Alkali injured CXCR5 +/+ mouse corneas showed significantly increased mRNA ( p < 0.001) and protein ( p < 0.01 or p < 0.0001) levels of the CXCR5 compared to the naïve corneas. Likewise, alkali injured CXCR5 −/− mouse corneas showed remarkably amplified inflammation in clinical eye exams in live animals. The histological and molecular analyses of these corneas post euthanasia exhibited markedly augmented inflammatory cells in H&E staining and significant CD11b + cells in immunofluorescence ( p < 0.01 or < 0.05); and tumor necrosis factor-alpha ( TNFα ; p < 0.05), cyclooxygenase 2 ( COX-2; p < 0.0001), interleukin ( IL)-1β ( p < 0.0001), and IL-6 ( p < 0.0001 or < 0.01) mRNA expression compared to the CXCR5 +/+ mouse corneas. Interestingly, CXCR5 −/− alkali injured corneas also showed altered mRNA expression of fibrotic alpha smooth muscle actin ( α-SMA; p > 0.05) and angiogenic vascular endothelial growth factor ( VEGF; p < 0.01) compared to the CXCR5 +/+ alkali injured corneas. In summary, the CXCR5 gene is expressed in all three major layers of the cornea and appears to influence corneal inflammatory and repair events post-injury in vivo . More studies are warranted to tease the mechanistic role of CXCR5 in corneal inflammation and wound healing . Highlights: CXCR5 gene is expressed in human and mouse corneal epithelial, stromal fibroblasts, and endothelial cells. CXCR5 expression augmented significantly post injury in mouse cornea in vivo. CXCR5 deficiency led to modified inflammatory, fibrotic, and angiogenic markers in alkali injured cornea in vivo.